Standardization of plant growth regulators for successful tissue culture of sweet potato (Journal of the Bangladesh Agricultural University, 2018)
The experiment was carried out during the period from June 2016 to January, 2017 at the Plant Biotechnology Laboratory, Department of Horticulture, Patuakhali Science and Technology University (PSTU) for in vitro regeneration of sweet potato. In this study, the nodal segment explants and different combinations of growth regulators were used for in vitro regeneration of sweet potato. BAP (6-benzylamino purine) and KIN (Kinetin) were used for in vitro shoot regeneration and IBA (Indole-6- Butyric Acid) with NAA (Naphthalene Acetic Acid) were used for in vitro root regeneration. The highest percentage of shoot initiation (91.30), the minimum number of days (9.00) for shoot initiation, the highest number of shoot/plantlet (11.00) and the highest shoot length (4.38 cm) was observed when nodal segment explants cultured on MS medium supplemented with BAP 1.5 mg/L + KIN 0.1 mg/L. On the other hand, the highest root initiation percentage (94.12), the minimum number of days (6.00) for root initiation, the highest number of root/plantlet (9.33) and the highest root length (11.13 cm) was observed in the MS medium supplemented with IBA 0.5 mg/L + NAA 0.1 mg/L. Regenerated plantlets were acclimatized for 5 days and adopted in soil by 6-7 days of transplantation.J. Bangladesh Agril. Univ. 16(2): 178-181, August 2018